If They Do Call You a Nurse, It Is Always a "Male Nurse": Experiences of Men in the Nursing Profession. Issue 1 (5th February 2013) - Rajacich, Dale; Kane, Deborah; Williston, Courtney; Cameron, Sheila
Abstract : Background and Purpose: Men are underrepresented in nursing, accounting for less than 6% of Canadian nurses. This research explores issues surrounding recruitment, retention, and work life satisfaction for men who are nurses working in acute care settings Method and Findings: Purposive and snowball sampling was used in this descriptive, qualitative study. Sixteen men participated in four focus groups conducted in three communities in southwestern Ontario. The participants revealed that work stress, lack of full‐time opportunities, and gender‐based stereotypes contributed to job dissatisfaction. Providing care to patients and making a difference were personal rewards that influenced their desire to stay in the profession. To promote nursing as a viable profession, unrestricted by gender, the participants recommended that recruitment strategies begin at an earlier age. Discussion and Conclusion: Findings are discussed in relation to recruitment and retention issues with implications for education, practice, and management.